Comparison of Matlab’s multivariate analysis for qualitative and quantitative electronic taste sensing system - Abdul Hallis, Abdul Aziz; Ammar, Zakaria; Ali Yeon, Md Shakaff, Prof. Dr.; Abdul Rahman, Saad; Abdul Hamid, Adom, Prof. Madya Dr.; Maz Jamilah, Masnan (Universiti Malaysia Perlis (UniMAP), 2010)
1st Regional Conference on Applied and Engineering Mathematics (RCAEM-I) 2010 organized by Universiti Malaysia Perlis (UniMAP) and co-organized by Universiti Sains Malaysia (USM) & Universiti Kebangsaan Malaysia (UKM), 2nd - 3rd June 2010 at Eastern & Oriental Hotel, Penang.